PENGEMBANGAN MODUL PEMBELAJARAN IPA (SCIENCE) BERBASIS KARAKTER UNTUK SISWA TK DI SEKOLAH CINTA KASIH SORONG - Stefany Margareta Martono (LPPM Politeknik Saint Paul Sorong, 2020)
The development of a Character-Based Science Learning Module for Kindergarten students at Cinta Kasih Sorong School is a module development that can help teachers in providing science (Science) material as well as training skills and encouraging student development intellectually and training students to have a characterist attitude. The purpose of this research is the development of modules to make interesting learning so that students can develop cognitive independently through science learning combined with character-based methods. The module development design of this study uses the research and development method or